2011
DOI: 10.3892/mmr.2011.674
|View full text |Cite
|
Sign up to set email alerts
|

LY294002 enhances cytotoxicity of temozolomide in glioma by down-regulation of the PI3K/Akt pathway

Abstract: Abstract. The introduction of temozolomide (TMZ) has advanced chemotherapy for malignant gliomas. However, a considerable number of glioblastoma (GBM) cases are refractory to TMZ. Previous studies have revealed that the PI3K/ Akt pathway is activated in an ataxia telangiectasia and Rad3 related-dependent manner in response to TMZ. Thus, we hypothesized that PI3K inhibitors may act as antitumor agents against gliomas and potentiate the cytotoxicity of TMZ. The cytotoxicity of a PI3K inhibitor, LY294002, was exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…In addition, TMZ combined with amlexanox e caciously reduced the tumor volume and improved the survival of mice in the xenograft model in vivo. To date, a growing number of studies have focused on the inhibition of the AKT signaling pathway with combined administration in GBM and other tumors [7,[29][30][31][32][33][34]. Zhiyun Yu and his colleagues suggested that TMZ combined with NVP-BEZ235 synergistically inhibited GBM cell proliferation though downregulating AKT/mTOR signaling pathway [4], which was similar to our ndings.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, TMZ combined with amlexanox e caciously reduced the tumor volume and improved the survival of mice in the xenograft model in vivo. To date, a growing number of studies have focused on the inhibition of the AKT signaling pathway with combined administration in GBM and other tumors [7,[29][30][31][32][33][34]. Zhiyun Yu and his colleagues suggested that TMZ combined with NVP-BEZ235 synergistically inhibited GBM cell proliferation though downregulating AKT/mTOR signaling pathway [4], which was similar to our ndings.…”
Section: Discussionsupporting
confidence: 85%
“…TMZ induced AKT activation, as well as deactivated mTOR. It has proved that inhibition of AKT expression was accompanied by a significant increased in glioma cell sensitivity to TMZ [ 9 , 13 ]. These results strongly support the hypothesis that clinical benefits are obtained by combining TMZ with inhibitors of the AKT-mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…AKT activation is also correlated with the increased tumorigenicity, invasiveness and stemness [ 7 ]. It has demonstrated that cancer stem cells are preferentially sensitive to an inhibitor of AKT [ 8 , 12 ] and down-regulation of the AKT pathway can enhance the cytotoxicity of TMZ [ 9 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Akt activation is correlated with the increased tumorigenicity, invasiveness and stemness ( 6 ) and overexpression of an active form of Akt increases glioma cell resistance to TMZ ( 5 , 8 ). It has demonstrated that cancer stem cells are preferentially sensitive to an inhibitor of Akt ( 7 , 10 ) and down-regulation of the PI3K/Akt pathway enhances the cytotoxicity of TMZ ( 11 ). At present, the most effective drug for the treatment of glioblastoma is TMZ, the primary path leading to glioma cell death is formation of O-6-methylguanine and apoptotic signalling triggered by O-6-methyl G:T mispairs, but apoptotic signalling goes through a step mediated by AMPK ( 12 ).…”
Section: Introductionmentioning
confidence: 99%